β1- and β2-adrenergic receptor mediated spontaneous contractions and ryanodine receptor channel opening in human failing heart - Weilan Mo; Nicole A. Beard; Katherine T. Gillette-Browne; Karen Hay; Elizabeth Cheesman; Alexander Dashwood; Melanie Spratt; Annalese B. Semmler; Yee Weng Wong; Haris Haqqani; Derek R. Laver; Torsten Christ; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
In heart failure, β-adrenergic receptor (β-AR)-Gsα-cAMP-protein kinase A (PKA) signalling predisposes to delayed-afterdepolarisation-mediated arrhythmias. Phosphodiesterases (PDEs) hydrolyse cAMP, and PDE3 restrains β 1 -AR, β 2 -AR-mediated inotropic responses in failing hearts from β-blocker-treated patients. Whether these receptors provoke arrhythmias through ryanodine receptor (RyR2) dysregulation, and how PDE activity and prior β-blockade treatment modify this, is undefined. We sought to define how β 1 -AR and β 2 -AR activation provokes arrhythmias through RyR2 mechanisms in explanted human failing hearts, and how PDE activity and prior β-blocker therapy modulate this response. A diastolic model of ventricular arrhythmia using human right ventricular trabeculae with pacing stopped was used. Trabeculae were exposed to (-)-noradrenaline/(-)-adrenaline to activate β 1 -AR/β 2 -AR respectively with or without PDE inhibitors and monitored for spontaneous contractions. In parallel, sarcoplasmic reticulum vesicles from trabeculae were used to assess RyR2 channel function, phosphorylation and oxidation. Activation of β 1 -AR or β 2 -AR increased the frequency of spontaneous contractions, concomitant increases in diastolic RyR2 channel opening, phosphorylation and oxidation. Trabeculae from carvedilol-treated patients showed fewer β 2 -AR-mediated spontaneous contractions than those treated with β 1 -AR blockers. The PDE3 inhibitor cilostamide augmented β 2 -AR-mediated spontaneous contractions, RyR2 channel opening and Ser2808 phosphorylation. In human failing heart, β 1 -AR or β 2 -AR activation increased arrhythmic contractions associated with greater diastolic RyR2 channel opening, phosphorylation and oxidation. PDE3 attenuated β 2 -AR-mediated arrhythmic contractions, RyR2 channel opening and Ser2808 hyperphosphorylation. These findings suggest that combining β 1 - and β 2 -AR blockade with strategies that reduce RyR2 Ca 2+ leak and preserve RyR2-associated PDE3 activity may improve arrhythmia control in heart failure. Graphical abstract The arrhythmogenic human failing heart. Figure shows β 1 -AR, β 2 -AR mediated arrhythmia mechanisms in human HF. Activated β 1 -AR or β 2 -AR couple to the Gsα-protein-adenylyl cyclase signalling pathway to increase cyclic AMP, activation of PKA with consequent phosphorylation of RyR2. Other changes to RyR2 include oxidation and dissociation of FKBP12.6 (Walweel et al. 2017; Denniss et al. 2020). The changes contribute to Ca 2+ leak from the sarcoplasmic reticulum through RyR2 during diastole to cause outward transport of Ca 2+ /inward transport of Na + through the Na + /Ca 2+ exchanger resulting in DAD induced action potentials, depolarization of the myocyte and arrhythmic contractions (Walweel et al. 2017; Denniss et al. 2020). The β 2 -AR pathway that mediates arrhythmia generation is under the control of PDE3 (this paper).

Positive inotropic effects of serotonin in atrial EHT: further proof for an atrial phenotype? - Muhammed Sönmez; Margaret Nandudu; Paul Brunnbauer; Carl Schulz; Birgit Klampe; Thomas Schulze; Arne Hansen; Thomas Eschenhagen; Torsten Christ (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) cultured in the presence of retinoic acid were proposed as a model for human atrium. Since in the human heart positive inotropic effects of serotonin (5-HT) are restricted to the atrium, we investigated whether the presence of 5-HT responses may distinguish between hiPSC-atrial and ventricular CM. Nonfiltered retinoic acid (1 µM) was used to induce an atrial phenotype (hiPSC-aCM) in two different hiPSC lines. Untreated hiPSC-CM were used as controls (ventricular). We measured 5-HT4 receptor ( HTR4 ) expression and 5-HT effects on Ca 2+ currents (I Ca ), force, and action potential in engineered heart tissue (EHT). HTR4 transcript abundance was five times higher in atrial EHT. 5-HT (100 µM) increased I Ca from 5.3 ± 0.8 to 8.1 ± 1.1 pA/pF, prolonged APD 20 from 8.1 ± 1.2 to 12.0 ± 1.2 ms, and shortened APD 90 from 142.3 ± 11.3 to 117.0 ± 6.6 ms in hiPSC-aCM, but not in hiPSC-vCM. 5-HT increased force in atrial EHTs from 0.06 ± 0.01 to 0.10 ± 0.01 mN but not in vEHT. Spontaneous beating rate per minute was increased by 5-HT in aEHT from 151.3 ± 7.5 to 173.7 ± 4.1 and in vEHT from 43.1 ± 4.2 to. 61.3 ± 3.4. Both EHTs contain functional 5-HT receptors, but 5-HT increases I Ca and force only in aEHT, similar to the human heart. In vEHT, 5-HT’s positive chronotropic effect in the absence of I Ca stimulation and inotropic response suggests activation of funny channels. Our findings demonstrate that aEHT shares the typical atrial-selective regulation of I Ca and force by 5-HT, thus making aEHT a promising model to study 5-HT 4 receptors in the human heart.

Tribute to Alberto J. Kaumann - Torsten Christ; Ursula Ravens (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
This review summarises the major contributions of Alberto J. Kaumann who died in December 2024. The German-born pharmacologist devoted his scientific life to the cardiovascular adrenergic and serotinergic systems. He classified the subtypes of the cardiac β-adrenoceptors (β-AR) into β 1 - and β 2 -AR using the subtype-selective antagonist. In addition, he showed that the dual coupling of β 2 -AR to Gα s - and Gα i -proteins plays a minor role in the healthy heart. He also found that the positive inotropic effect of serotonin (5-HT) was not mediated by release of noradrenaline, but due to activation of a specific 5-HT receptor coupled to Gα s -proteins. His experiments with prostaglandin-E 1 demonstrated an increase in cAMP and spontaneous beating frequency of the heart in the absence of a positive inotropic effect, suggesting a compartmentation of cAMP. This finding was later verified by experiments with subtype-selective phosphodiesterase inhibitors. Last not least, he explained the antiarrhythmic effect of sotalol by prolongation of the cardiac action potential duration, providing for the first time, what was years later to be defined as class III antiarrhythmic action. With Alberto Kaumann, we have lost a colleague and friend who had dedicated his life to science and music.

Sex differences in human atrial electrophysiology: the dark side of the moon? Will engineered heart tissue help to bring light into the darkness? - Djemail Ismaili; Junsoo Im; Renate B. Schnabel; Thomas Eschenhagen; Torsten Christ (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Sex-related differences in cardiac electrophysiology are well established in the ventricle and have reached textbook level. In contrast, our understanding of sex effects in the human atrium remains limited, despite clear clinical observations such as the lower incidence of atrial fibrillation (AF) in women. In this review, we summarize sex differences and discuss potential reasons for the imbalance in knowledge, including the lack of ECG markers for atrial repolarization, the minimal contribution of I Ks in atrial tissue, and possible sex differences in inward rectifier currents. We also address the role of aging and hormonal changes, the complexity of studying the perimenopausal transition, and the current limitations of available models. Finally, we highlight the potential of engineered heart tissues to detect genetically encoded differences and to dissect genomic versus non-genomic hormone effects.

Modulating cardiac physiology in engineered heart tissue with the bidirectional optogenetic tool BiPOLES - Barbora Schwarzová; Tim Stüdemann; Muhammed Sönmez; Judith Rössinger; Bangfen Pan; Thomas Eschenhagen; Justus Stenzig; J. Simon Wiegert; Torsten Christ; Florian Weinberger (Pflügers Archiv - European Journal of Physiology, 2023)
Optogenetic actuators are rapidly advancing tools used to control physiology in excitable cells, such as neurons and cardiomyocytes. In neuroscience, these tools have been used to either excite or inhibit neuronal activity. Cell type–targeted actuators have allowed to study the function of distinct cell populations. Whereas the first described cation channelrhodopsins allowed to excite specific neuronal cell populations, anion channelrhodopsins were used to inhibit neuronal activity. To allow for simultaneous excitation and inhibition, opsin combinations with low spectral overlap were introduced. BiPOLES (Bidirectional Pair of Opsins for Light-induced Excitation and Silencing) is a bidirectional optogenetic tool consisting of the anion channel Guillardia theta anion-conducting channelrhodopsin 2 (GtACR2 with a blue excitation spectrum and the red-shifted cation channel Chrimson. Here, we studied the effects of BiPOLES activation in cardiomyocytes. For this, we knocked in BiPOLES into the adeno-associated virus integration site 1 (AAVS1) locus of human-induced pluripotent stem cells (hiPSC), subjected these to cardiac differentiation, and generated BiPOLES expressing engineered heart tissue (EHT) for physiological characterization. Continuous light application activating either GtACR2 or Chrimson resulted in cardiomyocyte depolarization and thus stopped EHT contractility. In contrast, short light pulses, with red as well as with blue light, triggered action potentials (AP) up to a rate of 240 bpm. In summary, we demonstrate that cation, as well as anion channelrhodopsins, can be used to activate stem cell–derived cardiomyocytes with pulsed photostimulation but also to silence cardiac contractility with prolonged photostimulation.

Impact of phosphodiesterases PDE3 and PDE4 on 5-hydroxytryptamine receptor4-mediated increase of cAMP in human atrial fibrillation - Bernardo Dolce; Torsten Christ; Nefeli Grammatika Pavlidou; Yalin Yildirim; Hermann Reichenspurner; Thomas Eschenhagen; Viacheslav O. Nikolaev; Alberto J Kaumann; Cristina E Molina (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
Atrial fibrillation (AF)–associated remodeling includes contractile dysfunction whose reasons are only partially resolved. Serotonin (5-HT) increases contractile force and causes arrhythmias in atrial trabeculae from patients in sinus rhythm (SR). In persistent atrial fibrillation (peAF), the force responses to 5-HT are blunted and arrhythmic effects are abolished. Since force but not arrhythmic responses to 5-HT in peAF could be restored by PDE3 + PDE4 inhibition, we sought to perform real-time measurements of cAMP to understand whether peAF alters PDE3 + PDE4-mediated compartmentation of 5-HT 4 receptor-cAMP responses. Isolated human atrial myocytes from patients in SR, with paroxysmal AF (paAF) or peAF, were adenovirally transduced to express the FRET-based cAMP sensor Epac1-camps. Forty-eight hours later, cAMP responses to 5-HT (100 μM) were measured in the absence or concomitant presence of the PDE3 inhibitor cilostamide (0.3 μM) and the PDE4 inhibitor rolipram (1 μM). We successfully established real-time cAMP imaging in AF myocytes. 5-HT increased cAMP in SR, paAF, and peAF, but in line with previous findings on contractility, this increase was considerably smaller in peAF than in SR or paAF. The maximal cAMP response to forskolin (10 μM) was preserved in all groups. The diminished cAMP response to 5-HT in peAF was recovered by preincubation with cilostamide + rolipram. We uncovered a significantly diminished cAMP response to 5-HT 4 receptor stimulation which may explain the blunted 5-HT inotropic responses observed in peAF. Since both cAMP and force responses but not arrhythmic responses were recovered after concomitant inhibition of PDE3 + PDE4, they might be regulated in different subcellular microdomains.

Application of the RIMARC algorithm to a large data set of action potentials and clinical parameters for risk prediction of atrial fibrillation - Ursula Ravens; Deniz Katircioglu-Öztürk; Erich Wettwer; Torsten Christ; Dobromir Dobrev; Niels Voigt; Claire Poulet; Simone Loose; Jana Simon; Agnes Stein; Klaus Matschke; Michael Knaut; et al. (Medical & Biological Engineering & Computing, 2015)

Prostaglandin E2 does not attenuate adrenergic-induced cardiac contractile response - Simon Pecha; Eileen Mudersbach; Klaus-Dieter Söhren; Samer Hakmi; Hermann Reichenspurner; Thomas Eschenhagen; Torsten Christ (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Carvedilol induces greater control of β2- than β1-adrenoceptor-mediated inotropic and lusitropic effects by PDE3, while PDE4 has no effect in human failing myocardium - Peter Molenaar; Torsten Christ; Emanuel Berk; Andreas Engel; Katherine T. Gillette; Alejandro Galindo-Tovar; Ursula Ravens; Alberto J. Kaumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Inhibition of IK,ACh current may contribute to clinical efficacy of class I and class III antiarrhythmic drugs in patients with atrial fibrillation - Niels Voigt; Nadiia Rozmaritsa; Anne Trausch; Thomasz Zimniak; Torsten Christ; Erich Wettwer; Klaus Matschke; Dobromir Dobrev; Ursula Ravens (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Transmural expression of ion channels and transporters in human nondiseased and end-stage failing hearts - Ewa Soltysinska; Søren-Peter Olesen; Torsten Christ; Erich Wettwer; Andras Varró; Morten Grunnet; Thomas Jespersen (Pflügers Archiv - European Journal of Physiology, 2009)

Chelerythrine treatment influences the balance of pro- and anti-apoptotic signaling pathways in the remote myocardium after infarction - Gregor Simonis; Stephan Wiedemann; Kerstin Schwarz; Torsten Christ; Daniel G. Sedding; Xinjian Yu; Rainer Marquetant; Ruediger C. Braun-Dullaeus; Ursula Ravens; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2008)

Electrophysiological profile of propiverine – relationship to cardiac risk - Torsten Christ; Erich Wettwer; Melinda Wuest; Manfred Braeter; Frank Donath; Pascal Champeroux; Serge Richard; Ursula Ravens (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Risperidone-induced action potential prolongation is attenuated by increased repolarization reserve due to concomitant block of ICa,L - Torsten Christ; Erich Wettwer; Ursula Ravens (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

An aqueous extract of the marine sponge Ectyoplasia ferox stimulates L-type Ca2+-current by direct interaction with the Cav1.2 subunit - Torsten Christ; Melinda Wst; Jan Matthes; Michael Jnchen; Susanne Jrgens; Stefan Herzig; Erich Wettwer; Dobromir Dobrev; Klaus Matschke; Dietrich Mebs; Ursula Ravens (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)